JOHN KEATSS SENSUOUS IMAGERY IN"WHEN I HAVE FEARS THAT I MAY CEASE TO BE" - Suryo Tri Saksono (TEFLIN Journal: A publication on the teaching and learning of English, 2011)
Abstract: When I have fears that I may cease to be, by John Keats, porÂtrays the poets fear of dying young and being unable to fulfill his ideal as a writer and loses his beloved. Based on the use of sensuous imagery, it is clear that visual image dominates the use of imagery and there are two major thought groups: 1) Keats expresses his fear of dying young (lines 1-12); he fears that he will not fulfill himself as a writer (lines 1-8) and that he will lose his beloved (lines 9-12); 2) Keats resolves his fears by asserting the unimportance of love and fame in the concluding two and a half lines.